A family intervention to reduce delirium in hospitalised ICU patients: A feasibility randomised controlled trial. (June 2017) - Mitchell, Marion L.; Kean, Susanne; Rattray, Janice E.; Hull, Alastair M.; Davis, Chelsea; Murfield, Jenny E.; Aitken, Leanne M.
Abstract: Background: Family members could play an important role in preventing and reducing the development of delirium in Intensive Care Units (ICU) patients. This study sought to assess the feasibility of design and recruitment, and acceptability for family members and nurses of a family delivered intervention to reduce delirium in ICU patients. Method: A single centre randomised controlled trial in an Australian medical/surgical ICU was conducted. Sixty-one family members were randomised (29 in intervention and 32 in non-intervention group). Following instructions, the intervention comprised the family members providing orientation or memory clues (family photographs, orientation to surroundings) to their relative each day. In addition, family members conducted sensory checks (vision and hearing with glasses and hearing aids); and therapeutic or cognitive stimulation (discussing family life, reminiscing) daily. Eleven ICU nurses were interviewed to gain insight into the feasibility and acceptability of implementing the intervention from their perspective. Results: Recruitment rate was 28% of eligible patients (recruited n = 90, attrition n = 1). Following instruction by the research nurse the family member delivered the intervention which was assessed to be feasible and acceptable by family members and nurses. Protocol adherence could be improved with alternative data collection methods. Nurses considered the activities acceptable. Conclusion: The study was able to recruit, randomise and retain family member participants. Further strategies are required to assess intervention fidelity and improve data collection.